ENCOUNTERING BARRIERS: INSIGHTS ON HEALTH PROMOTION IMPLEMENTATION IN COMMUNITY HEALTH CENTERS - Nasution, Sri Lestari Ramadhani; Girsang, Ermi; Manalu, Putranto; Anggita, Nindi Dwi; Febrianty, Novita Dwi; Sianipar, Milka Rositi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Community Health Centers (Puskesmas) are crucial in promoting health and empowering communities to maintain their health independently. Despite their importance, health promotion programs have faced significant challenges, leading to suboptimal implementation. This study aims to analyze the implementation of health promotion programs at Puskesmas and identify the barriers faced by implementers. Qualitative research with a case study design was conducted at four Community Health Centers in Serdang Bedagai Regency from December 2021 to March 2022. In-depth interviews involved the heads of the Community Health Centers, the responsible individuals for health promotion programs at the centers, and community health cadres. A total of 12 participants underwent in-depth interviews to deeply explore information regarding policy aspects, funding, facilities, and human resources. Additionally, data were collected through observation and documentation. Data analysis followed the protocol developed by Miles and Huberman. The study results indicate that implementing health promotion at Community Health Centers has not been optimal due to barriers such as program funding availability, inadequate supporting facilities, and a shortage of competent human resources. This research contributes to the existing literature by providing a detailed examination of the specific challenges faced by Puskesmas in implementing health promotion programs. It emphasizes the need for targeted interventions to strengthen these centers' operational capabilities. To ensure optimal outcomes, stakeholders must focus on adequate budget allocation, the provision of supporting facilities, and training for program implementers.